If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6z + -1) + -4(z + 9) = 4(z + 1) Reorder the terms: 3(-1 + 6z) + -4(z + 9) = 4(z + 1) (-1 * 3 + 6z * 3) + -4(z + 9) = 4(z + 1) (-3 + 18z) + -4(z + 9) = 4(z + 1) Reorder the terms: -3 + 18z + -4(9 + z) = 4(z + 1) -3 + 18z + (9 * -4 + z * -4) = 4(z + 1) -3 + 18z + (-36 + -4z) = 4(z + 1) Reorder the terms: -3 + -36 + 18z + -4z = 4(z + 1) Combine like terms: -3 + -36 = -39 -39 + 18z + -4z = 4(z + 1) Combine like terms: 18z + -4z = 14z -39 + 14z = 4(z + 1) Reorder the terms: -39 + 14z = 4(1 + z) -39 + 14z = (1 * 4 + z * 4) -39 + 14z = (4 + 4z) Solving -39 + 14z = 4 + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. -39 + 14z + -4z = 4 + 4z + -4z Combine like terms: 14z + -4z = 10z -39 + 10z = 4 + 4z + -4z Combine like terms: 4z + -4z = 0 -39 + 10z = 4 + 0 -39 + 10z = 4 Add '39' to each side of the equation. -39 + 39 + 10z = 4 + 39 Combine like terms: -39 + 39 = 0 0 + 10z = 4 + 39 10z = 4 + 39 Combine like terms: 4 + 39 = 43 10z = 43 Divide each side by '10'. z = 4.3 Simplifying z = 4.3
| 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 | | 5b*6b= | | 3x*5x*2x= | | 6(2z-1)-2(z+3)=3(z+1) | | 20y-10=10 | | 3a*4a= | | b/14=5/10 | | X+(-4)+2x=14 | | 9-10x=77-38x | | -18x^2+65x+7=0 | | 3x^3-7x^2=-10 | | 9d-2d+6d-6=6d | | y/8=2/10 | | (3+5x^2)(3-5x^2)= | | 3x^3-7x^2=10 | | 9x-7=6x+16 | | (2x+3)2-3x-4=0 | | 16a^3b+4ab=0 | | 6+9+6= | | 12X^3+3X^2-24X^2-6X=0 | | (x+2)(x+8)=72 | | 5s+12=0 | | (3d^4-4d^3+6)(-3c^2d)= | | 12X^3+3X^2-24X-6X=0 | | -x^2+5x=3 | | (3d^4-4d^3+6)(-3cd)= | | 4(6X-5)2= | | 6d+3d-5d-8=2d | | 9n=8n+24 | | 3x-9=2x+15 |